Optimization of crankpin bearing lubrication under dynamic loading considering effect of micro asperity contact. Issue 10 (7th May 2020) - Nguyen, Vanliem; Wu, Zhenpeng; Le, Vanquynh
Abstract : Purpose: To improve the lubrication and tribology performance (LTP) of the crankpin bearing, this paper aims to propose the optimization of the crankpin bearing parameters considering effect of the high-speed dynamic load and micro asperity contact. Design/methodology/approach: A numerical simulation method combined by the slider-crank-mechanism dynamic and lubrication models is applied to solve the dynamic and lubrication equations of crankpin bearing. These equations are then computed via an algorithm program written in Matlab software. The contact force (Wac ) in the asperity contact region, friction force (Ff ) and friction coefficient ( μ ) of crankpin bearing are chosen as objective functions. The original parameters and experimental data of the engine are used for the simulation to enhance the reliability of the research results. The parameters are then optimized to obtain the minimum values of Wac, Ff and μ . Findings: The research results show that the LTP is significantly improved with optimized parameters. Particularly, the maximum values of Wac and Ff are greatly decreased by 27 and 32%, respectively. Originality/value: Reducing the width, radius and surface roughness and increasing the radial clearance of crankpin bearing can improve better the LTP. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-02-2020-0072/